2023
DOI: 10.3389/fphys.2023.1149840
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the effects of nutrition, age, and behavioral caste on honey bee physiology, immunity, and colony health

Abstract: Nutritional stress, especially a dearth of pollen, has been linked to honey bee colony losses. Colony-level experiments are critical for understanding the mechanisms by which nutritional stress affects individual honey bee physiology and pushes honey bee colonies to collapse. In this study, we investigated the impact of pollen restriction on key markers of honey bee physiology, main elements of the immune system, and predominant honey bee viruses. To achieve this objective, we uncoupled the effects of behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…Similarly to our results, one study [67] found that inhibition of defensin-1 can occur in parallel to the activation of the RNAi pathway in DWV-B inoculated bees. Our study shows that there may be concurrent inhibition of the melanisation pathway, which was not the case in other studies [40,68]. Conversely, when observed, AMP production was activated on 6 dpi but not on 3 dpi, confirming that AMPs are used as a late defence system that may remain active for longer times [61].…”
Section: Discussionsupporting
confidence: 57%
“…Similarly to our results, one study [67] found that inhibition of defensin-1 can occur in parallel to the activation of the RNAi pathway in DWV-B inoculated bees. Our study shows that there may be concurrent inhibition of the melanisation pathway, which was not the case in other studies [40,68]. Conversely, when observed, AMP production was activated on 6 dpi but not on 3 dpi, confirming that AMPs are used as a late defence system that may remain active for longer times [61].…”
Section: Discussionsupporting
confidence: 57%
“…However, less is known about differences between young and old foragers. Only a few studies addressed this question [ 114 , 115 ]. The correlation with the gene set specific for the cAMP second messenger pathway can explain the higher sensitivity of the high performer bees compared to their low performing counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…While we assumed that the lack of nutritional diversity could be a factor affecting colony health; however, this assumption must be considered cautiously, and further analysis of the protein contribution provided by this type of pollen is required. Nevertheless, several studies have demonstrated the impact of nutritional stress, revealing a positive relationship between multi oral areas and the annual survival of hives 49,50 .…”
Section: Discussionmentioning
confidence: 99%